1982
DOI: 10.1113/expphysiol.1982.sp002672
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stimulation of the Left Atrial Receptors in the Cat

Abstract: SUMMARYIn the cat, distension of the left atrial appendages by means of small balloons resulted in variable changes in the heart rate. Distension of the junctions between the upper two left pulmonary veins and the left atrium resulted in a small but statistically significant increase in the heart rate. Distension did not result in any significant changes in the blood pressure. The increases in heart rate are far less than observed in the dog and it is suggested that the atrial receptors might play a less impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1985
1985
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Vatner & Zimpfer (1981) found in conscious baboons, weighing from 20 to 25 kg, that rapid volume expansion always resulted in an increase in heart rate; whereas in small conscious baboons no effect on heart rate was observed following a similar intervention. Scott et al (1982) found that the responses of an increase in afferent atrial receptor discharge and an increase in heart rate to distension of small balloons at the pulmonary vein-atrial junctions in the cat were smaller than those previously obtained in the dog (Linden & Kappagoda, 1982).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Vatner & Zimpfer (1981) found in conscious baboons, weighing from 20 to 25 kg, that rapid volume expansion always resulted in an increase in heart rate; whereas in small conscious baboons no effect on heart rate was observed following a similar intervention. Scott et al (1982) found that the responses of an increase in afferent atrial receptor discharge and an increase in heart rate to distension of small balloons at the pulmonary vein-atrial junctions in the cat were smaller than those previously obtained in the dog (Linden & Kappagoda, 1982).…”
Section: Discussioncontrasting
confidence: 41%
“…For instance, in some reports the reflex increases in heart rate and urine flow were not consistently obtained in response to stimulation of the atrial receptors by interventions such as volume expansion, distension of balloons in the left atrium or the pulmonary vein-atrial junctions, and head-out immersion in small animals such as monkeys and cats (Zucker & Gilmore, 1975;Gilmore & Zucker, 1978 a, b;Vatner & Zimpfer, 1981;Cornish & Gilmore, 1982;Scott, Roberts & Tierney, 1982). The complexity of the diffuse stimulus and the small responses related to the small size of the atrium may have resulted in an inconsistency of response.…”
Section: Discussionmentioning
confidence: 99%